Aesthetic Transformation of Video4Change Project Through Postmodernism Studies - Sazkia Noor Anggraini (IJCAS (International Journal of Creative and Arts Studies), 2014)
Related research on community videos commonly limited in the social domain. This may happen because making video community is not classified as work of art, but rather as a tool to convey messages on community organizing method. Video4Change (v4c) project here consist different organizations in four countries; Indonesia, India, America and Israel. The review of videos conducted in textual and visual ethnography. This method used to specify all the things captured in the sense, the visual, the voice (audio) and the symbol on each video. Video as a medium in the postmodernism era considered as an illusion and simulation, now has more authority. Video build new structures and functions that transformed from mere aesthetic imagery into practical media with particular meanings. The video made by common people has been taking control of society to understanding the images by interpret it. This research attempts to trace and shift the study of community video from the perspective of art, vice versa from what have done before. However, the video as a tool has particular rules and approach to effectively deliver ‘text’ or message in visual language. This study expected to be a reference in a cultural context that comes from the artistic perspective. The analysis will shift the meaning of aesthetic perspective that could be transforming into practical solution-based. Beyond that, this study is able to see how the perspective transforms as the co modification of art in society changes.